In vitro and in vivo toxicity evaluation of halloysite nanotubes. Issue 44 (23rd July 2018) - Long, Zheru; Wu, Yan-Ping; Gao, Hua-Ying; Zhang, Jun; Ou, Xianfeng; He, Rong-Rong; Liu, Mingxian
Abstract : Halloysite is weakly toxic to cells and can be excreted out through the gastrointestinal metabolism of zebrafish. Abstract : Because of their outstanding properties, increasing numbers of research studies and emerging applications for manufacturing products are currently in progress for halloysite nanotubes (HNTs). Therefore, the impact of HNTs on the environment and human health should be taken into consideration. In order to clearly show the cell uptake of HNTs and the biodistribution of HNTs in zebrafish, HNTs are labeled with fluorescein isothiocyanate (FITC-HNTs). The cytotoxicity assays showed that the cell viabilities of human umbilical vein endothelial cells (HUVECs) and human breast adenocarcinoma (MCF-7) cells were above 60% after being treated with different concentrations of HNTs (2.5–200 μg mL −1 ) for 72 h. Confocal laser scanning microscopy (CLSM) results showed the uptake of HNTs by HUVECs and MCF-7 cells. The in vivo toxicity of HNTs was then investigated in the early development of zebrafish embryos. The percent survival of zebrafish embryos and larvae showed no significant changes at different developmental stages (24, 48, 72, 96, and 120 hpf) when treated with various concentrations of HNTs (0.25–10 mg mL −1 ). Besides, HNTs could promote the hatchability of zebrafish embryos and did not affect the morphological development of zebrafish at a concentration of ≤25 mg mL −1 . HNTs could also be ingested by zebrafish larvae and accumulated predominantly in the gastrointestinal tract. The fluorescence intensity of FITC-HNTs decreased gradually with time, which suggested that HNTs could be excreted by zebrafish larvae through the gastrointestinal metabolism. Therefore, it can be concluded that HNTs are relatively biocompatible nanomaterials, which can be utilized in many fields.